Ultrasensitive digital quantification of cytokines and bacteria predicts septic shock outcomes - M. Fatih Abasıyanık (Nature Portfolio, 2020)
Ultrasensitive methods for detection of biomarkers for infectious disease are needed for diagnosing, monitoring and targeting treatment. Here the authors develop a digital assay for inflammatory markers, bacterial DNA and antibotic-resistance genes and apply it to characterise asthma patients and predict mortality from septic shock.